Eco-innovation and the development of business models lessons from experience and new frontiers in theory and practice - Azevedo, Susana Garrido; Brandenburg, Marcus 1972-; Carvalho, Helena; Cruz-Machado, Virgilio (Greening of Industry Networks Studies, 2014)
Environmental challenges such as pollution, climate change, water and natural resources depletion and dwindling bio-diversity are true threats to the survival of our civilization, forcing us to learn how to act now. Fortunately this is exactly what this book does: presenting real life cases, along with theory, methodologies and tools demonstrating how eco-innovation can support sustainable economic growth and save our planet for future generations. Following an introduction describing developments and directions of eco-innovation, Section One discusses Models and Frameworks Supporting Eco-Innovation, with chapters on search strategy for radical eco-innovation; and systematic eco-innovation with TRIZ Methodology. Section Two offers surveys and case studies showing eco-innovation in practice, including a sketch of the eco-innovative landscape in the Brazilian Cellulose, Paper and Paper Products Industry; efforts to eco-innovate among large Swedish companies; progress towards joint product-service business models and more. The third section surveys future directions and emerging trends, among them a new methodology for eco-friendly construction; the development of lightweight small inter-island ferries in Scandinavia and BioTRIZ: a win-win methodology for eco-innovation. The book explores eco-innovation as a framework for supporting the development of new business models which consider the entire business ecosystem, on the way to a sustainable world. Moreover, it explores the eco-innovation process in cross-national and cross-sector perspective